Determination of Poverty through Unemployment in North Sumatra - Piter Andrean; Marliyah Marliyah; Maryam Batubara (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to analyze the effect of the unemployment rate, Gross Regional Domestic Product (GRDP), investment, and The Human Development Index (HDI) which are relevant in influencing poverty in North Sumatra Province. This study uses secondary data in the form of North Sumatra Cross Section data from 2015-2021. The analytical method used in this study is a mixed method with Path Analysis and Descriptive Qualitative approaches. The results showed that GRDP had a significant effect on the poverty rate, Investment had a significant effect on poverty, HDI had a significant effect on poverty, GRDP had a significant effect on unemployment, Investment had a significant effect on unemployment, HDI had a significant effect on unemployment, and unemployment has no significant effect on poverty in North Sumatra. Unemployment does not function as an intervening variable between GRDP and poverty, unemployment functions as an intervening variable between investment and poverty, and unemployment does not function as an intervening variable between HDI and poverty.